Problems of diagnostics and treatment of breast phyllodes tumors - Van Shu; A. A. Artemieva; E. A. Busco; V. V. Semiglazov; T. Y. Semiglazova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
The study revealed that in case of standard survey of patients with phyllodes tumors (PT), mistakes are made in 66 % of cases. The use of a sonoelastography and ultrasonography with contrasting allows avoiding errors in most cases. Long-term results of treatment correlate with the PT subgroup. Recurrence–free (overall survival) figures in case of benign PT are reliably higher than in case of malignant PT. Limited excision of the tumor is followed by highly frequent local recurrence in case of any subgroup of PT (30 %). Lumpectomy is also followed by highly frequent local recurrence that first of all concerns malignant PT (57 %). The main options for surgical treatment of malignant PT are breast amputation or a mastectomy.